2014
DOI: 10.1161/circresaha.115.304351
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Alteration of PCSK9 With In Vivo CRISPR-Cas9 Genome Editing

Abstract: Rationale Individuals with naturally occurring loss-of-function PCSK9 mutations experience reduced blood low-density lipoprotein cholesterol (LDL-C) levels and protection against cardiovascular disease. Objective The goal of this study was to assess whether genome editing using a clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas) system can efficiently introduce loss-of-function mutations into the endogenous PCSK9 gene in vivo. Methods and Results We used adenovirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
321
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 466 publications
(333 citation statements)
references
References 10 publications
5
321
2
5
Order By: Relevance
“…Adenovirus-mediated delivery of Cas9 has been used to achieve in vivo genome editing in mouse lungs (Maddalo et al, 2014) and livers Ding et al, 2014;Wang et al, 2015a).…”
Section: Delivery Of Genome-editing and Epigenome-editing Agentsmentioning
confidence: 99%
“…Adenovirus-mediated delivery of Cas9 has been used to achieve in vivo genome editing in mouse lungs (Maddalo et al, 2014) and livers Ding et al, 2014;Wang et al, 2015a).…”
Section: Delivery Of Genome-editing and Epigenome-editing Agentsmentioning
confidence: 99%
“…NHEJ-mediated disruption of one or more of these genes should have a therapeutic effect. Proof-of-concept studies with PCSK9 in mouse models have demonstrated that CRISPR-Cas9 genome editing of the gene can occur with high efficiency in the adult liver, reducing blood PCSK9 levels by up to 90% and blood cholesterol levels up to 40% [5][6][7][8]. While there is concern for off-target effects, in other words, mutations occurring at sites other than the target gene, so far the proof-of-concept studies have found little evidence of this phenomenon in vivo, although the currently used techniques are not sensitive enough to detect mutations occurring in less than one in 10,000 cells.…”
Section: Somatic Therapymentioning
confidence: 99%
“…and a 40% decrease in the levels of cholesterol in the blood. 78 Gene editing can also be used to eliminate or target viral genomes. In the context of the liver, the elimination of hepatitis B virus can be achieved in preclinical models by using CRISPRCas9, TALENs, and ZFNs nuclease platforms.…”
Section: Key Pointmentioning
confidence: 99%